Une approche géographique du tourisme intérieur dans un pays émergent : l’exemple du Brésil - Nicolas Le Brazidec (Confins)
Tourism is not any more the prerogative of occidental societies. A tremendous boom of tourist flows in the emerging nations characterized the end of the twentieth century. As well as their increasing integration in globalization, this new deal contributes to change our minds about the countries of the Global South. It also leads us to question about the landscapes, the spatial forms, the actors and the challenges of this tourism development. In the same way, the question of logics of imitation or, on the contrary, singularization, between the touristic practices of the countries of the Global North and those of the Global South, arises. The example of Brazil leads us to study these socio-economic evolutions and these territorial dynamics, by showing in particular that international flows, providers of currencies, often occult the extent of domestic tourism flows. It also shows that the two types of tourism are organized in a differentiated way within the Brazilian territory. Little attended by the foreign tourists – with the exception of the Argentinians - the South of Brazil is a perfect place to study domestic tourism. The extensive analysis of Balneário Camboriú and Gramado, two tourist places from this part of the country, aims at clarifying the methods of the setting in tourism of places whose site and situation are rather distinct. The first one, localized on the littoral between Florianópolis and Curitiba, constitutes the principal seaside resort of the State of Santa Catarina. The second one is located at 800 meters above sea level, on the plateaus at the north of Porto Alegre (Rio Grande do Sul). Despite their similarities in the chronology of their tourist development, Balneário Camboriú was created ex nihilo by the tourist activity whereas Gramado preexisted and was invested by tourism. Especially, their trajectories rather early differed, according to the choices carried out by the local actors. The massification of tourism in Balneário Camboriú contrasts with the rather elitist character of Gramado. Nowadays, one takes part in a touristic conurbation whose spreading out continues, while the other endeavors to build an image of idealized village which one can be described as “disneylandized”. However, in any case, the tourist frequentation maximizes social interactions (real ones or supposed ones) clean to satisfy the search of sociability, social distinction and, more generally, otherness of those which go there. This is a universal characteristic of tourist places.